"Clinical triad" findings in pediatric Klippel-Feil patients. Issue 1 (December 2016) - Samartzis, Dino; Kalluri, Prakasam; Herman, Jean; Lubicky, John; Shen, Francis
Abstract Background It has been propagated that patients with Klippel-Feil syndrome (KFS) exhibit "clinical triad" findings (CTFs), known as a short neck, low posterior hairline, and limited cervical range of motion (ROM). However, the literature has noted that up to 50 % of KFS cases may not present with such findings and the reasoning behind such assertions remains speculative. As such, the following study addressed the association between CTFs to that of congenitally-fused cervical segments and other risk factors in KFS patients. Methods We conducted a retrospective clinical study based on prospectively collected radiographic data. Thirty-one KFS patients at a single institution were assessed. Radiographs were used to evaluate the location and extent of congenitally-fused segments (spanning the occiput (O) to the first thoracic vertebra (T1)), as well as examining coronal and sagittal cervical alignments based on the Samartzis et al. KFS classification. Clinical records were evaluated to account for the initial clinical assessment of CTFs. Patients were further stratified into two groups: Group 1 included patients noted to have any CTFs, while Group 2 included patients who had no such findings. Results There were 12 males and 19 females (mean age at initial consultation: 9.7 years). No evidence of any of the CTFs was shown in 35.5 % of patients, whereas 38.7, 16.2 and 9.7 % were determined to have one, two or all three criteria, respectively. Limited cervical ROM was the most common finding (64.5 % of patients). In Group 1, 25 % had a short neck, 30 % a low posterior hairline, and 100 % exhibited limited cervical ROM. Group 1 had a mean of 3.9 fused cervical segments, whereas Group 2 had a mean of 2.5 fused cervical segments (p = 0.028). Age, sex-type, occipitalization and alignment parameters did not significantly differ to Group-type (p > 0.05). In Group 1, based on the Samartzis et al. Types I, II, and III, 16.7, 73.3, and 80.0 % of the patients, respectively, had at least one CTF. Conclusions Complete CTFs were not highly associated during the clinical assessment of young KFS patients. However, KFS patients with extensive, congenitally-fused segments (i.e. Samartzis et al. Type III) were significantly more likely to exhibit one of the components of the CTF, which was predominantly a limited cervical ROM. Clinicians managing young pediatric patients should not rely on the full spectrum of CTFs and should maintain a high-index of suspicion for KFS, in particular in individuals that exhibit associated spinal findings, such as congenital scoliosis.